Seasonal Precipitation and Soil Moisture Relationships Across Forests and Woodlands in the Southwestern United States. Issue 4 (20th April 2021) - Koehn, C. R.; Petrie, M. D.; Bradford, J. B.; Litvak, M. E.; Strachan, S.
Abstract: Precipitation [P: mm] controls forest and woodland dynamics in the southwestern United States (SWUS) by altering soil moisture [ θ : mm 3 mm −3 ] availability, but the influence of P on θ is complex, varying across space and time. We evaluated seasonal P and θ relationships at shallow (0–20 cm) and intermediate (50 cm) soil depths for nine semiarid forest and woodland sites (56 total years), which comprised three elevation gradients in the SWUS. We developed time‐varying definitions of winter (snow accumulation), spring (moisture recharge), and summer (moisture deficit), and determined how these sites exhibited similar P influence on θ across depths in the soil profile, between seasons, and in seasons with above‐ and below‐average P. Higher elevation sites (>2, 800 m) experienced greater winter P, longer springs, and shorter summers compared to lower elevation sites (<2, 500 m). Seasons with above‐ and below‐average P reduced elevation‐associated differences. θ at 0–20 cm was generally decoupled from θ at 50 cm in seasons with average and below‐average P, imparted by differences in spring and summer rainfall versus winter snowfall. Notably, across‐season influence of θ (e.g., a season's similarity to subsequent seasons) was high when the first season experienced above‐ or below‐average P, and the subsequent season experienced average P, illustrating an important temporal connection initiated by wet and dry conditions. These results illustrate similarities in P‐ θ relationships across widely differing ecosystems in the SWUS, and elucidate how these relationships may be altered in a changing climate. Plain Language Summary: Soil moisture is an important and limiting resource for forests and woodlands in the southwestern US, and is controlled by precipitation patterns that differ widely across the region. We evaluated winter (snowfall, rainfall) and spring and summer (rainfall) relationships to soil moisture at shallow (0–20 cm) and intermediate (50 cm) soil depths at nine diverse forest and woodland sites in this region. Using a novel approach that defined winter, spring, and summer by their soil moisture patterns, we investigated how precipitation at these sites influenced soil moisture across soil depths, between seasons, and in seasons with high and low precipitation. Higher elevation sites had greater winter precipitation, longer springs, and shorter summers than lower elevation sites, but years with high or low precipitation reduced these differences. Across all sites, shallow soil moisture had little similarity to intermediate soil moisture, yet moisture at both shallow and intermediate soil depths could be strongly influenced by previous seasons with substantially lower or higher precipitation. Our study illustrates similarity in how precipitation influences soil moisture availability across diverse forest and woodland ecosystems in this region, and elucidates fundamental relationships that govern how they respond to seasonal variation in climate. Key Points: Differing forest and woodland ecosystems show similarities in precipitation and soil moisture relationships that inform future functioning Timing of soil moisture defined seasons differs between high and low elevations, yet differences are reduced by low or high precipitation Shallow and deeper soil moisture are often physically disconnected, yet are shaped by low and high seasonal precipitation similarly